Prep for the perfect score (Albany, NY, 2016)
Peterson’s ACT® Prep Guide 36 is an advanced test prep resource for competitive students who want to maximize their already good ACT test scores. This guide also preps first-time test takers who know the basic concepts, consider standard practice questions in other guides too easy, and plan to score high on their initial ACT test.
Keywords: Đại học và Cao đẳng,Universities and colleges; Kỳ thi đầu vào,Entrance examinations; Hoa Kỳ,United States